The Allocation of Incentives in Multilayered Organizations: Evidence from a Community Health Program in Sierra Leone - Deserranno, Erika; Caria, A. Stefano; Kastrau, Philipp; León-Ciliotta, Gianmarco (Journal of Political Economy, 2025)
Does the allocation of incentives across the hierarchy of an organization matter for its performance? In an experiment with a large public health organization, we find that health care provision is highly affected by how incentives are allocated between frontline workers and their supervisors. Sharing incentives equally between these two layers raises health visits by 61% compared with unilateral allocations and uniquely improves health service provision and health outcomes. We provide reduced-form and structural evidence that effort complementarities and contractual frictions drive these results and explore the implications for the optimal design of incentive policies in multilayered organizations.